Morfometria corpórea, características do sêmen, proteínas seminais e testosterona em cervos Cervus unicolor, em cativeiro - Chacur, Marcelo George Mungai; Martins, Ellyn Amanda Fonseca; Silva, Aline Aparecida da; Guaberto, Luciana Machado; Gabriel Filho, Luís Roberto Almeida [UNESP]; Sanches, Osimar de Carvalho; Oba, Eunice [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
The aim of this work was to study the body morphometry, semen characteristics, seminal plasma protein profile in SDS-PAGE and serum testosterone concentration in Sambar Deer (Cervus unicolor), in captivity in the breeding season (spring). Four males aged between 12 and 36 months were assessed in four moments with intervals of seven days with body weight (60.5 to 89.0kg), body mass index (93.07 to 126.56kg/m2), ejaculate volume (0.50±0.35mL to 0.75±0.28mL), sperm motility (87.75±4.78% to 90.00±7.07% ), total defects (17.25±5.81% to 47.72±17.55%), serum testosterone (6.43±4.33 ng/dL to 166.00±64.48ng/dL) and seminal plasma proteins with bands between 7.6 and 142 kDa. The characteristics of ejaculates did not differ (P>0.05) among ejaculates (1st, 2nd and 3rd). There were differences (P<0.05) for sperm defects elevation on the fourth ejaculate. In seminal plasma 16 to 27 protein bands between 7.6 and 142 kDa were identified. In conclusion, sperm quality was satisfactory in the spring and the stress of successive contentions decreased sperm quality. Also, there is influence of age upon serum testosterone concentration which was higher in deer at 36 months.

Objetivou-se estudar a morfometria corpórea, as características do sêmen, o perfil proteico do plasma seminal em SDS-PAGE e a concentração sérica de testosterona em cervos-sambar (Cervus unicolor), criados em cativeiro, na estação reprodutiva da primavera. Quatro machos com idades entre 12 e 36 meses foram avaliados em quatro momentos, com intervalos de sete dias, com peso corpóreo (60,5 a 89,0kg), índice de massa corporal (93,07kg/m2 a 126,56kg/m2), volume do ejaculado (0,50±0,35mL a 0,75±0,28mL), motilidade espermática (87,75±4,78% a 90,00±7,07%), defeitos totais (17,25±5,81% a 47,72±17,55%), testosterona sérica (6,43±4,33ng/dL a 166,00±64,48ng/dL) e proteínas do plasma seminal com bandas entre 7,6 e 142kDa. As características dos ejaculados não diferiram (P>0,05) entre as três primeiras colheitas. Houve diferença (P<0,05) para os defeitos espermáticos com elevação na quarta colheita. No plasma seminal de cada cervo, foram identificadas de 16 a 27 bandas de proteínas entre 7,6 e 142kDa. Conclui-se que a qualidade espermática foi satisfatória na primavera. O estresse das contenções sucessivas causou queda da qualidade espermática. A idade influi na concentração sérica de testosterona, a qual foi maior nos cervos aos 36 meses.
Body morphometry, semen characteristics, seminal proteins and testosterone in sambar deer (Cervus unicolor) in captivity
Keywords: Cervidae; cativeiro; sêmen; SDS-PAGE; andrógeno; Cervidae; captivity; semen; SDS-PAGE; androgen